Análise do pulso labial no trompete por filtragem inversa - Gustavo Machado Oliveira (2020)
Blowing control is an essential element of the trumpet playing technique, especially when playing notes in the same position, however, direct measurement of the air pulse that passes through the lips in vibration is complicated and invasive. The sound production process of the trumpet is, in short, the result of the sum of the sound generated by the vibration of the lips with the resonances of the instrument tube and the sound radiation. This model of sound production of the trumpet can be compared to the model of speech production, referred to in the literature as a source-filter model, in which the source is the air flow that passes through the glottis, the filter is the resonances of the vocal tract and the sound radiation. This study is based on the approach of the source filter model of voice production to estimate the air flow that passes through the trumpet player vibrating lips. We propose to model the sound production of the trumpet by reverse filtering using an algorithm proposed by P. Alku (1992) for the analysis of voice production. We were able to obtain the excitation patterns produced by the lips by applying the inverse of the transfer function of the trumpet tube to the output signal captured in the instrument's bell for notes performed with the same position. The inverse filter was able to estimate the lip pulse of trumpet players in a non-invasive way. We used the middle of the notes (sustain) as the region of analysis, where the signal presented the greatest spectral stability and we extracted values of skewness and kurtosis from a cycle of the lip pulse signal obtained to analyze and compare its characteristics. The results showed that the opening of the lips in high notes performed on the trumpet occurs more abruptly than on low notes and the inverse filtering can be a great ally in obtaining information about the trumpet performance technique.